The Political Economy of Digital Monopolies : Contradictions and Alternatives to Data Commodification - Bilić, Paško; Žitko, Mislav, 1982-; Prug, Toni (Book collections on Project MUSE., 2021)
As outrage over the socially damaging practices of technology companies intensifies, this book asks what it actually means to hold a 'monopoly' in the tech world and offers an in-depth analysis of how these corporate giants are produced, financialized, and regulated.